PROLIFERATION OF SANDCRETE BLOCK INDUSTRIES IN NIGERIA: A QUALITY ASSESSMENT OF INDUSTRIAL MOULD BLOCKS IN BENIN CITY (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
The proliferation of sandcrete block industries in Nigeria has significantly impacted the construction sector. Sandcrete blocks serve as essential building materials, constituting over 90% of physical infrastructures in the country. These blocks are widely used for both load-bearing and non-load-bearing walls in Nigeria. This study focuses on the quality assessment of industrial mold blocks in Benin City, Nigeria. The objective is to evaluate the compliance of block manufacturers with specified standards. The research involves field studies, sampling, and laboratory experiments. The study revealed that some sandcrete blocks had low compressive strength values, as low as 0.66 N/mm². The water absorption capacity of certain blocks was as high as 16.95%, indicating poor quality. The study concludes that the quality of sandcrete blocks in the study area is not adequately compliant with the approved standards.